GAMBARAN FAKTOR-FAKTOR YANG TERKAIT DENGAN KINERJA PETUGAS DALAM PENEMUAN KASUS PADA PROGRAM TUBERKULOSIS PARU DI KABUPATEN GROBOGAN - Idha Setyowati; Lintang Dian Saraswati; Mateus Sakundarno Adi (Fakultas Kesehatan Masyarakat Universitas Diponegoro, 2018)
Case finding of tuberculosis (TB) is one of the main strategies of tuberculosis prevention. Case Notification Rate (CNR) in Grobogan Regency still under the achievements of Central Java. This study aims to describe the factors related to officer performance in case finding on pulmonary tuberculosis (TB) program in Grobogan regency. This research is a descriptive research with cross sectional approach conducted on 30 P2TB officers and 30 TB laboratory officers in health center in the work area of Grobogan Regency Health Office. The sample is the total study population. Not really good results were knowledge (56,7%), training history (71,7%), work motivation (56,7%), monitoring and evaluation (53,3%), workload (60,0%), incentive (55,0%), monitoring evaluation implementation (53,3%), suspect finding (60,0%), contact tracking (50,0%). The good results were have job satisfaction (53,3%), boss leadership (96,7%), microscopic sputum examination (53,3%). The work performance of the P2TB officers in a poor suspect netting is more in the older adult age (71,4%), having job satisfaction (68,8%), having work motivation (61,5%), a good leadership (62,1%). The work performance of the P2TB officers in a poor contact tracking is more in the older adult age (43,3%), having job satisfaction (50,0%), having work motivation (53,8%), a good leadership (51,7%). Suggestions that can be given to P2TB officers and laboratory staff are to increase that knowledge concerning method and media of health promotion and to use those knowledge as a stimulus to improve performance in TB case finding in health center.